MARKETING COMMUNICATION STRATEGY FOR PERSONAL SELLING CHACKERS MAHKOTA IN THE DIGITAL ERA - Pudjasetia, Faraby Alirsyad; Hariyanto, Didik (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the marketing communication strategies of the Krupuk Mahkota MSME in Kedungrejo Village, Jabon District, Sidoarjo Regency, with a particular focus on the effectiveness of personal selling in maintaining competitiveness in the digital era. Method: The research employed a descriptive qualitative approach using interviews, observations, and documentation to gain an in-depth understanding of marketing practices and consumer interactions. Results: The findings reveal that personal selling remains a highly relevant and effective strategy, as direct interaction, storytelling about the business journey, and friendly service foster consumer trust, emotional connection, and loyalty. Additionally, the strategy is enhanced through complementary sales promotions, such as periodic discounts and the use of customer testimonials, which strengthen the MSME’s brand image. Novelty: This study highlights that personal selling continues to serve as a distinctive competitive advantage for MSMEs amid digital transformation, demonstrating that human-centered communication offers an irreplaceable personal experience that digital promotional media alone cannot replicate.